The Transient Stability Study of a Synchronous Generator Based on the Rotor Angle Stability - Selwa Fetissi; Djamel Labed; Imen Labed (Institute of Advanced Engineering and Science, 2015)
Transient stability is an important aspect in the operation of electrical power system. In case of fault occurs in the system, the determining of fault clearing time of circuit breaker is considered one of the main factors to ensure power transfer of the system. This paper is aim to study the transient stability of single machine infinite bus system (SMIB), based on the rotor angle stability. The study is performed to determine the influence of the critical clearing time of the circuit breakers on the rotor angle stability of the generator in the case of three phase fault. For obtaining and determining numerically the nature of the rotor angle of machine, we applied the Step-by-step method for different values of fault clearing time. The results of simulation indicate that determine of critical clearing time is a major evaluation in stability studies. The system model is created in MATLAB/ SIMULINK software.